2013
DOI: 10.1088/0963-0252/22/1/015022
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electron energy distributions and discharge parameters in a dual frequency ICP discharge

Abstract: Using a radio frequency (RF) compensated Langmuir probe, modulations in electron energy distribution (EED) and plasma potential are investigated in a discharge produced by a large-area dual frequency/dual antenna inductively coupled plasma source. The discharge is ignited using two frequencies (2 and 13.56 MHz). It is observed that the EEDs can be tailored by varying the power ratio of the two frequencies. Increasing the power level of the low frequency (P 2 MHz) enhances the population density of high-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…10 It has also been demonstrated that, when using this type of plasma source, the ion and electron energy distribution could be efficiently modulated by varying the power ratio of the two frequencies. 11,12 Pulsing this plasma source could provide further advantages, since pulsed plasma has several benefits over continuous wave (CW) plasma, such as low charging damage, improvement of film quality in deposition, variation of ion species, and higher plasma density at the same average input power. Consequently, pulsed ICPs have recently attracted considerable interest in the field of integrated circuit fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has also been demonstrated that, when using this type of plasma source, the ion and electron energy distribution could be efficiently modulated by varying the power ratio of the two frequencies. 11,12 Pulsing this plasma source could provide further advantages, since pulsed plasma has several benefits over continuous wave (CW) plasma, such as low charging damage, improvement of film quality in deposition, variation of ion species, and higher plasma density at the same average input power. Consequently, pulsed ICPs have recently attracted considerable interest in the field of integrated circuit fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…18 By using this kind of plasma source, it has also been demonstrated that ion and electron energy distribution could be efficiently modulated by varying two power ratio. 19,20 A further advantage, such as more flexibility to control the discharge parameters, could be added, if this source is used in a pulsed mode. 18 Pulsed plasmas show significant potential to meet the majority of the scaling challenges and offer new tuning knobs (pulse frequency, duty cycle, and optional phase lag between source and bias pulses) that enhance independent control of plasma conditions (in particular, ion bombardment energy and plasma chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, the influence of the DF power ratio on the electron energy distribution, plasma density, electron temperature, and plasma potential has been investigated. 15 The results showed that the electron density increased, and the electron temperature and plasma potential decreased with the increasing LF power. In addition, Kim et al 16 reported that the plasma density produced in a DF ICP source was higher than in a SF ICP with the same total RF power.…”
mentioning
confidence: 95%
“…Therefore, considerable effort has been made on research into the DF ICP source, which consists of two matching coils, and could be used as an effective method to improve the uniformity in large-area ICPs. [13][14][15][16][17][18][19] Mishra et al 13 first investigated the plasma characteristics in a dual planar antenna ICP reactor, with the coil frequencies fixed at 2 MHz and 13.56 MHz, respectively. They observed that the best uniformity could be obtained by adjusting the LF powers when the high frequency power was fixed at 800 W. Subsequently, by using an energy-resolved quadrupole, they measured the time-averaged ion energy distribution (IED) in Ar=CF 4 discharges at various DF powers, and revealed that the DF ICP was an effective tool to tailor the IEDs and therefore affected the etch and deposition profiles.…”
mentioning
confidence: 99%